A Z‐Scheme‐Inspired Photobioelectrochemical H2O/O2 Cell with a 1 V Open‐Circuit Voltage Combining Photosystem II and PbS Quantum Dots. (13th December 2018) - Riedel, Marc; Wersig, Julia; Ruff, Adrian; Schuhmann, Wolfgang; Zouni, Athina; Lisdat, Fred
Abstract: A biohybrid photobioanode mimicking the Z‐scheme has been developed by functional integration of photosystem II (PSII) and PbS quantum dots (QDs) within an inverse opal TiO2 architecture giving rise to a rather negative water oxidation potential of about −0.55 V vs. Ag/AgCl, 1 m KCl at neutral pH. The electrical linkage between both light‐sensitive entities has been established through an Os‐complex‐modified redox polymer (POs ), which allows the formation of a multi‐step electron‐transfer chain under illumination starting with the photo‐activated water oxidation at PSII followed by an electron transfer from PSII through POs to the photo‐excited QDs and finally to the TiO2 electrode. The photobioanode was coupled to a novel, transparent, inverse‐opal ATO cathode modified with an O2 ‐reducing bilirubin oxidase for the construction of a H2 O/O2 photobioelectrochemical cell reaching a high open‐circuit voltage of about 1 V under illumination.